A critical view on hypoxia training: horse versus human - Moerman, W. (Ghent University, 2018)
Hypoxia training is a well-known training strategy to enhance performance in human athletes. The paradigm of hypoxia training is that hypoxia is induced by decreasing the partial pressure of oxygen in the air. This can be done either due to the decreased atmosphere pressure at high altitude, or due to an artificially decreased fractional concentration of oxygen in the air. This decreased partial pressure induces hematological and non-hematological adaptations, resulting in a more efficient oxygen supply to the tissues. This increased efficiency of oxygen supply enhances performance when competing in normoxia. Hypoxia training is becoming more popular in the equine world. This raises the question whether horses could benefit from hypoxia training. Although this is a well-known and popular strategy in humans, there is no consensus in human science about the effectiveness of hypoxia training in all its forms. Scientific literature, discussing hypoxia training in horses, is scarce. Little research has been done in the past, however, the topic is becoming more popular in recent years. A major obstacle for researchers, evaluating the hematological responses to hypoxia training in horses, is the storage of erythrocytes in the spleen of the horse. Small effects have been detected in horses. However, the effects are unconvincing due to equivocal results and a low number of horses, used in the studies. Nevertheless, the small effects that were detected indicate that hypoxia training might induce changes and even enhance performance in horses. Therefore, more research is needed with larger groups to clarify the effects of hypoxia training.